1985
DOI: 10.3168/jds.s0022-0302(85)80947-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lint on Whole Cottonseed Passage and Digestibility and Diet Choice on Intake of Whole Cottonseed by Holstein Cows

Abstract: Effects of rolling whole linted cottonseed and whole acid-delinted cottonseed on whole seed passage and digestibility were determined using 24 lactating Holstein cows. Whole seed passage averaged .74% in all cows fed whole linted seed during the standardization period and .45% in 6 cows fed whole linted seed during a comparison period, contrasted to 11.3% in 6 cows fed acid-delinted seed. Digestibility of ether extract was less in the 6 cows fed whole acid-delinted cottonseed. No advantage was for rolling whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 7 publications
2
21
0
2
Order By: Relevance
“…The nonlinted WCS used in the present study is less digested in the rumen than linted WCS (Coppock et al, 1985). Its lower digestibility may be related to its rapid sedimentation in the rumen.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The nonlinted WCS used in the present study is less digested in the rumen than linted WCS (Coppock et al, 1985). Its lower digestibility may be related to its rapid sedimentation in the rumen.…”
Section: Discussionmentioning
confidence: 70%
“…Whereas high linted dietary WCS is well digested by ruminants, digestibility of delinted cottonseed is lower. In lactating dairy cows, about 11 % of consumed whole acid-delinted seeds are excreted in the faeces (Coppock et al, 1985). Similar proportions of naturally nonlinted WCS of the Pima variety have been found in the faeces of lactating dairy cows (Sullivan et al, 1993).…”
Section: Introductionmentioning
confidence: 59%
“…However, a negative interaction was noted when a combination of cottonseed hulls and cotton long linter were fed to ruminants (Coppock et al, 1985; Sullivan et al, 1993). Palmquist (1995) observed that addition of cottonseed long fibre decreased fibre digestibility because it increased the pool size of undigested fibre in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…From their literature review, Arieli (1998) concluded that DM intake of dairy cattle is not altered when WCS is included at up to 25% of the diet. However, in some studies performed under hot weather conditions (Coppock et al, 1985a;Lanham et al, 1992), a decline in DM intake occurred with WCS feeding. This decline could be explained by the higher fiber content of the WCS diets in these experiments.…”
Section: Wcs Feeding and Dm Intakementioning
confidence: 90%
“…Most of the protein and fat of CS is contained within the meats, and most of the NDF is contained within the hull and the lint. Others (Coppock et al, 1985a;Sullivan et al, 1993a;Zinn, 1995;NRC, 2001;Prieto et al, 2003;McCaughey et al, 2005) reported that linted CS contained less CP and fat, and more NDF Table 1 Chemical composition of linted Upland and cracked Pima CS (Santos et al, 2002) Upland CS Cracked Pima CS …”
Section: Wcs Varieties and Its Chemical Compositionmentioning
confidence: 98%